LESSON LEARNED: BEST PRACTICE IMPLEMENTASI BUILDING INFORMATION MODELING (BIM) - Hermawan Hermawan (JoDA Journal of Digital Architecture, 2022)
In the past few decades, Building Information Modeling (BIM) has been widely used worldwide in industry of architecture, engineering dan construction (AEC). This scope is started from construction material manufacturing to construction project. So, this industry, which is one of the most complex industries, requires improvements in time and cost efficiency.. The purpose of this paper is to provide best practice of using BIM in buildings and infrastructure. The research method used in this research is project based evaluation. Project based evaluation is carried out on construction projects, namely building structures which include bored piles, pile cap, plates, shear walls, columns, and beams. The second project based evaluation is the bridge which focuses on structural work in single and double pillars. The results of research on building structures used as project based evaluations show that the difference in volume for each element ranges from 0.03% to 1.13%. with the total difference between conventional recalculation and modeling is around 0.358%. While the modeling in the second project based evaluation showed a volume difference of 12,965.66 kg for single pillar structures and 48,233.51 kg for double pillars. While the conventional method produces a larger estimated volume of 13,482.72 kg for single pillar structures and 49,827.70 kg for double pillars